2021
DOI: 10.1097/md.0000000000028390
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of secretory carcinoma arising from the oral minor salivary gland

Abstract: Introduction: Secretory carcinoma (SC) is a malignancy of the salivary glands, which is similar to SC of the breast regarding its association with neurotrophic tyrosine receptor kinase fusion-positive gene. SC is a recently described salivary gland tumor, and there are a few reports describing oral minor salivary gland-derived SC. We reported two cases of SC in the oral cavity and reviewed the literature. Patient concerns: The patients included a 65-year-old Japanese wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Out of a total of 226 studies published between 2010 and 2023, identified at initial search and screened for retrieval, 112 1–3,6–114 articles were included in the study, with a total of 674 patients described in these articles. The identification and screening process is described in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Out of a total of 226 studies published between 2010 and 2023, identified at initial search and screened for retrieval, 112 1–3,6–114 articles were included in the study, with a total of 674 patients described in these articles. The identification and screening process is described in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, clinical stage and high-grade transformation are the main adverse prognostic factors in which establishing an accurate histopathologic diagnosis, confirming the ETV6-NTRK3 fusion gene by genetic analysis is important both for diagnostic and prognostic purposes. [15][16][17] Currently, the guidelines for surgical treatment, chemoradiation, and follow up of these cases have not been standardized due to the small number of cases. 1) and negative immunostaining for Thyroglobulin, TTF1, DOG1, and CD117.…”
Section: Discussionmentioning
confidence: 99%